Mr. Harrison is embarrassin'! - Gutman, Dan.; Paillot, Jim. (New York : Scholastic, 2011)
When the power goes out in the school, everyone panics in the dark, and only nerdy Mr. Harrison, who can fix and build anything, can save the day.
"This edition is available for distribution only through the school market"--[P. 4] of cover.
560
Accelerated Reader AR
Keywords: Schools -- Juvenile fiction; Teachers -- Juvenile fiction